Geographic Information System (GIS) Based Predictive Study of Environmental Change in the Nigeria's Section of the Chad Basin - Dami, Anthony (2015)
The study characterized the spatial patterns of changes in land and water uses in the Chad basin between1963 and 2003; assessed the spatial patterns of land and water uses during the period; modeled future trends in environmental change in the area, and evaluated the strategies with which local communities were responding to the increasingly unfavourable environment of the Basin. These were with a view to providing an understanding of the dynamics of land and water uses in the basin.